A didactical framework for raising awareness of digital multiliteracies among university students: objectives, expectations and challenges - Azzam Alobaid (Discover Education)
Abstract In an era dominated by digital technologies, the concept of multiliteracies extends beyond traditional literacy skills to encompass digital media and information literacies. This article addresses the pressing need to raise awareness of digital multiliteracies among university students by proposing a comprehensive didactical framework. The purpose is to provide educators and policymakers with a structured approach to integrating digital multiliteracies into higher education. The framework explores objectives, expectations, and challenges, drawing from foundational and contemporary theories, including the epistemology of ignorance and postdigital literacy ecology. It aims to balance digital and traditional literacies while addressing equity and ethical considerations. Strategies for implementation include curriculum integration, workshops, peer learning, institutional support, and continuous assessment. By framing these ideas within a coherent theoretical structure, this article offers actionable insights for fostering critical, ethical, and lifelong learners prepared for a digitally interconnected world.